(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This study attempted to investigate the actual problems in teaching English as well as the solutions taken by the English teachers at schools. A number of difficulties emerged, partly coming from students, partly from teachers, and partly from the school’s facility. Students are challenged by their lack of vocabulary mastery, low concentration, lack of discipline, lack of interest, boredom, and speaking problem. Meanwhile, teachers’ challenges are shortage of teachers’ training, language proficiency problem, limited mastery of teaching methods, unfamiliarity to IT, and lack of professional development.